Firefly based distributed synchronization in Wireless Sensor Networks for passive acoustic localization - Verreycken, Walter Erik; Laurijssen, Dennis; Daems, Walter; Steckel, Jan (International Conference on Indoor Positioning and Indoor Navigation, 2016)
Passive acoustic localization is an important technique in a wide variety of monitoring applications, ranging from healthcare over biological survey to structural health monitoring of buildings. If the subject of interest emits a recognizable sound and is picked up by a distributed array of microphones it is possible to measure the difference in arrival times and reconstruct the source positions. This requires the microphones to be synchronized up to a fraction of the expected time differences of arrivals in order for the system to be able to produce accurate location estimates. In this paper we take a closer look at the techniques required to synchronize a network of sensors, connected through a low-power RF-communication link, in a distributed manner, ie. without the presence of a master node. The absence of a master node makes the network more robust against the failure of a single node. We took inspiration from the synchronization technique observed in some species of fireflies. A synchronized pseudo random number is embedded in the captured data as a marker to re-align the data-streams in time in a post-processing stage.